2013
DOI: 10.3109/10428194.2013.784758
|View full text |Cite
|
Sign up to set email alerts
|

Influence of methylenetetrahydrofolate reductase gene polymorphisms on the outcome of pediatric patients with non-Hodgkin lymphoma treated with high-dose methotrexate

Abstract: High-dose methotrexate (MTX) is a key component of most treatment protocols for childhood and adolescent non-Hodgkin lymphoma (NHL). Recent studies have suggested that the toxicity of antifolate drugs, such as MTX, is affected by inherited single nucleotide polymorphisms (SNPs) in folate metabolizing genes. The aim of our study was to investigate the potential influence of the C677T and A1298C genetic variants of the methylenetetrahydrofolate reductase (MTHFR) gene on the clinical toxicity and efficacy of MTX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Of them, 14 articles were excluded after title and abstract assessment, while 31 articles met the crude inclusion criteria and were further evaluated. Among these remaining 31 publications, we further excluded two studies1526 that were covered by other included investigations2024, three case-only designed studies404142, and one more study in which genotype frequency data in the controls for both of the C677T and A1298C polymorphisms were deviated from HWE ( P = 0.009 for C677T and P = 0.040 for A1298C)38. Overall, 25 articles were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of them, 14 articles were excluded after title and abstract assessment, while 31 articles met the crude inclusion criteria and were further evaluated. Among these remaining 31 publications, we further excluded two studies1526 that were covered by other included investigations2024, three case-only designed studies404142, and one more study in which genotype frequency data in the controls for both of the C677T and A1298C polymorphisms were deviated from HWE ( P = 0.009 for C677T and P = 0.040 for A1298C)38. Overall, 25 articles were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In stark contrast to the lack of studies on folate deficiency and toxicity of HD-Mtx, there have been a good number of studies in the literature which examined the association of MTHFR genotype with the complications of HD-Mtx. [ 8 9 10 11 12 ] Though this issue was investigated by various authors no consensus could be reached, and results have been mutually contradictory. The differences may have cropped in due to various reasons like sample size issues, non-uniform chemotherapy protocols including the dosage of Mtx and leucovorin.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Nine studies found the C677T mutation in MTHFR contributed to myelotoxicity. [53][54][55][56][57][58][59][60] The A1298C SNP was also associated with myelotoxicity in three studies 53,54,57 although two studies found this polymorphism to be protective. 61,62 Only a single study associated the G80A SNP with myelotoxicity.…”
Section: Myelotoxicitymentioning
confidence: 99%